Landraces in the Zemplén mountains the first target area of the collection mission program 2013-2014 - Ponicsánné Gyovai, Ágnes; Kollár, Zsuzsanna; Peti, Erzsébet; Horváth, Balázs; Oláh, Imre; Szalkovszki, Ottó; Baktay, Borbála (JOURNAL OF LANDSCAPE ECOLOGY, 2013)
As a part of a two years program for collecting plant genetic resources in Hungary and its neighbouring countries, a collection mission conducted in the Zemplén Mountains has revealed a range of diversity of locally grown traditional varieties. These varieties and landraces are cultivated by elderly home gardeners and there is an urgent need to conserve their varieties in gene bank. Traditional knowledge still existing on landrace maintenance may also form a basis for the local NGO’s on-farm conservation activities. Without the establishment of the Pannon Seedbank some wild species and the richness of the Pannonian flora may be threatened by extinction. In order to make the Pannon Seed Bank operational, seed samples of the Hungarian wild plant species need to be collected. One of the main aims of collecting missions is to collect valuable wild species of the region. During mission in the Zemplén 32 accessions of 30 species were collected, species with nature conservation importance were the followings: Gymnadenia conopsea (L.) R. Br)., Linum flavum L., Chamaecytisus albus (Hacq.) Rothm.).